DNA barcoding and phylogenetic relationship of shrimps (Crustacea: Decapoda) of Bangladesh (Bioresearch Communications, 2021)
We adopted DNA barcoding technique using a 658-bp fragment of the mitochondrial cytochrome c oxidase I (COI) gene to identify shrimp species collected from the different areas of Bangladesh. A total of 24 sequences were generated belonging to 14 species including four new records- Macrobrachium nipponense, Macrobrachium kistnense, Exopalaemon carinicauda and Alpheus malleator. Genetic distance measured with Kimura 2 parameter showed that genetic divergence increased with higher taxonomic rank. The mean genetic divergence was evaluated and found to be 0.935%, 22.67% and 30.92% within species, genus and family, respectively. In addition to the barcode-based species identification system, phylogenetic relationships were established where individuals belonging to the same species were grouped under the same clade. Maximum likelihood (ML) was preferred as the statistical method and as expected, the phylogenetic tree complemented and ensured the conventional taxonomy. The present study evidently showed that DNA barcoding can be served as an effective tool to discriminate the shrimp species and this will enhance the understanding on evolution and conservation biology.Bioresearch Commu. 7(1): 941-946, 2021 (January)